Novel Physiology and Definition of Poor Ovarian Response; Clinical Recommendations - Antoine Abu-Musa (International Journal of Molecular Sciences, 2020)
Poor ovarian response (POR) to controlled ovarian stimulation (OS) presents a major challenge in assisted reproduction. The Bologna criteria represented the first serious attempt to set clear criteria for the definition of POR. However, the Bologna criteria were questioned because of the persistent heterogeneity among POR patients and the inability to provide management strategies. Based on these facts, a more recent classification, the POSEIDON (Patient-Oriented Strategies Encompassing IndividualizeD Oocyte Number) classification, was developed to provide a homogeneous and refined definition of POR that significantly reduces the heterogeneity of the Bologna criteria definition of POR and helps in the clinical handling and counseling of patients. In this review, we discuss the impact of the POSEIDON classification on the clinical management of patients with POR.